RANCANG BANGUN SISTEM PAKAR KONSULTASI SISWA BERMASALAH DENGAN METODE FORWARD CHAINING BERBASIS WEB DI SMP MUHAMMADIYAH 1 WELERI - Kurniawan Catur Ristanto (STEKOM PRESS, 2019)
Problems that occur in students will be able to affect student learning processes. Even more problems that deviate from the prevailing social norms that can jeopardize the establishment of the system social. The design of this expert consulting system for problem students is based on the website using the method forward chaining with the aim to help analyze the causes of problems of students and subsequently the teacher counseling guidance to follow up on the results of student consultations. This expert system uses the Depth First Search (DFS) search technique and forward chaining as the inference method. The results of alpha and betha testing on the expert system indicate the expert system is feasible based on a questionnaire on alpha and betha testing.